Development of the nurse's communication ability with angry patients scale and evaluation of its psychometric properties. (25th February 2021) - Chen, Xi; Luo, Liumei; Jiang, Ling; Shi, Liumin; Yang, Li; Zeng, Yuting; Li, Fang; Li, Li
Abstract: Aims: To develop the Nurse's Communication Ability with Angry Patients Scale (NCAAPS) and evaluate its psychometric properties. Design: An instrument development and validation study. Methods: The survey was administered to 501 nurses from different emergency departments in China between 2 August 2019 and 3 October 2019. Data from 456 completed questionnaires were analysed to identify the factor structure of the NCAAPS. Results: The content validity index was satisfactory. Four factors were included and 71.25% of the total variance was explained by 19 items in NCAAPS. Confirmatory factor analysis supported the four‐factor structure. Cronbach's α coefficient was 0.96 for the overall scale and 0.81–0.92 for its subscales. Test–retest reliability was 0.740. Conclusion: We consider the NCAAPS to be a useful tool for measuring the ability of nurses to communicate with angry patients. Impact: It is anticipated that this new scale will help educators to identify specific areas of deficiency that could be targeted with training to improve the ability of nursing staff to communicate with angry patients.